2014
DOI: 10.1038/cddis.2014.467
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of autophagy by polyphenolic compounds as a potential therapeutic strategy for cancer

Abstract: Autophagy, a lysosomal degradation pathway for cellular constituents and organelles, is an adaptive and essential process required for cellular homeostasis. Although autophagy functions as a survival mechanism in response to cellular stressors such as nutrient or growth factor deprivation, it can also lead to a non-apoptotic form of programmed cell death (PCD) called autophagy-induced cell death or autophagy-associated cell death (type II PCD). Current evidence suggests that cell death through autophagy can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
181
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(191 citation statements)
references
References 128 publications
(145 reference statements)
8
181
0
2
Order By: Relevance
“…The data from the present study demonstrated that the overexpression of Beclin-1 may inhibit tumor cell migration, which also suggests that Beclin-1 expression is associated with tumor invasion in gastric cancer. Novel autophagy-based interventions, including Bcl-2 family regulation, caspase-dependent cleavage of autophagy-related gene protein and microRNA mimics to downregulate Beclin-1 have already been clinically or experimentally applied, suggesting promising approaches for novel clinical treatments (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…The data from the present study demonstrated that the overexpression of Beclin-1 may inhibit tumor cell migration, which also suggests that Beclin-1 expression is associated with tumor invasion in gastric cancer. Novel autophagy-based interventions, including Bcl-2 family regulation, caspase-dependent cleavage of autophagy-related gene protein and microRNA mimics to downregulate Beclin-1 have already been clinically or experimentally applied, suggesting promising approaches for novel clinical treatments (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…While apoptosis fulfills this role by removing damaged or unwanted cells, autophagy maintains cellular homeostasis by recycling selective intracellular organelles and proteins, and thus is considered an important protective mechanism for cancer cells in response to chemotherapy [25] . However, autophagy may help to induce apoptosis under certain conditions or lead to a non-apoptotic form of programmed cell death (PCD) called autophagic cell death or autophagyassociated cell death (type II PCD) [26] . Thus, the function of autophagy as cell death or cell survival machinery in different cases needs to be established.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Opipari et al presented the first evidence that resveratrol promotes cell death via autophagy in five ovarian cancer cell lines, which implied resveratrol as a promising regime in treating apoptosis-resistant cancer cells [166]. In addition, quercetin has antitumorigenic effects linked to its capacity for targeting key tumorigenic pathways such as mTOR/ elF4E-BP1/P70S6K signaling in ovarian cancer [167]. All the evidence demonstrates that many phytochemical compounds present in diets not only are inherently lesser toxicity but may also give novel therapeutic strategies in the treatment of ovarian cancer.…”
Section: Nutraceuticals and Traditional Medicinesmentioning
confidence: 99%